VACCINOPROPHYLAXIS OF CERVICAL CANCER: NEW CLINICAL DATA - L.S. Namazova-Baranova (Union of pediatricians of Russia, 2009)
Cervical cancer is one of the main causes of death in the patients with malignant tumors. Over 40% of cases involving this pathology are diagnosed at advanced stages. The etiological agent causing the development of cervical cancer is the persistence of Human papillomavirus (HPV) strains with high oncogenic risk. Currently the only available method of preventing HPV-caused diseases is vaccination. The article describes the results of Phase III multi-site doubt blind randomized research into the efficacy of vaccine against HPV (PATRICIA - Papilloma Trial against Cancer in young Adults), involving over 18,000 women aged 15 to 25 years from 14 countries in Europe, Asia, Latin and North Americas.Key words: cervical cancer, human papillomavirus, vaccinal prevention.